The Effect of Using the Smart Apps Creator on Science Learning Outcomes of Class VII Student of MTSN 2 Sidrap - Rahmatullah, Rahmatullah; M, Usman; Takdir, Muhammad; Hermansyah, Sam (International Journal of Educational Narratives, 2023)
Background. The population in this study were all seventh grade students of Madrasah Tsanawiyah Negeri 2 Sidrap and the sample in this study were students of class VII A Madrasah Tsanawiyah Negeri 2 Sidrap. Purpose. There are 2 variables in this study, the first independent variable is the effect of using the Smart Apps Creator application (x) and the second dependent variable is the learning outcomes of students in class VII A Madrasah Tsanawiyah Negeri 2 Sidrap (y). This research was conducted at Madrasah Tsanawiyah Negeri 2 Sidrap. Method. This study uses quantitative methods and experimental research type which aims to examine the effect of using Smart Apps Creator application on science learning outcomes of seventh grade students of Madrasah Tsanawiyah Negeri 2 Sidrap. Results. The results of this study concluded that there was an effect of using the Smart Apps Creator application on the science learning outcomes of Class VII Madrasah Tsanawiyah Negeri 2 Sidrap. Conclusion. This shows that the working hypothesis which states that there is an effect of using the Smart Apps Creator application on the science learning outcomes of seventh grade students of Madrasah Tsanawiyah Negeri 2 Sidrap is accepted.